POLYGAMY BETWEEN ETHICS AND LAW: A COMPARATIVE ANALYSIS OF MUHAMMAD ABDUH’S AND MUHAMMAD SAYYID TANTAWI’S QUR’ANIC INTERPRETATIONS - Bagas Pangestu; Yeti Dahliana (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The interpretation of polygamy-related verses in Islam remains a subject of continuous debate in both academic discourse and social practice. Al-Manar Tafsir by Muhammad Abduh and Al-Wasith Tafsir by Muhammad Sayyid Tantawi represent two distinct trends of modern Islamic thought in interpreting Surah an-Nisa verse 3. This study aims to analyze and compare the methodological approaches and conclusions of both exegetes regarding polygamy. Employing a qualitative method with a comparative literature-based approach, this research examines primary tafsir texts alongside relevant secondary sources. The findings reveal that Muhammad Abduh adopts a reformist interpretation emphasizing substantive justice and moral responsibility, thereby imposing strict limitations on polygamy. In contrast, Muhammad Sayyid Tantawi views polygamy within an applicable Islamic legal framework, considering material justice and social benefit in modern contexts. This study concludes that these interpretative differences reflect the dynamic nature of Islamic thought in responding to social change and contemporary challenges.